Bifunctional role of Pd/MMT-K 10 catalyst in direct transformation of furfural to 1,2-pentanediol - Date, Nandan S.; Chikate, Rajeev C.; Roh, Hyun-Seog; Rode, Chandrashekhar V. (Catalysis Today, 2018)
The acid functionality of montmorillonite clay K 10 (MMT-K 10) was found to play a key role to give 1,2-pentanediol (1,2-PeDO) in Pd catalysed furfural hydrogenation. Among various Pd loadings on MMT-K 10, 3% Pd/MMT-K 10 catalyst exhibited excellent performance giving almost complete conversion of FFR and the highest selectivity of 66% to 1,2-PeDO. Py-IR of the catalyst evidenced the presence of Brønsted acidity which was responsible in C5-O cleavage of furan ring after the formation of furfuryl alcohol which is the first step intermediate in FFR hydrogenation. At a lower temperature of 140 °C, highest selectivity of 56% was achieved for FAL while increase in temperature to 220 °C, enhanced the selectivity to 1,2-PeDO. Keeping the temperature constant at 220 °C, with increase in H2 pressure from 500 to 750 psig, resulted in decrease in 1,2-PeDO selectivity from 66 to 34% with proportionate increase in THFAL selectivity. Thus as per the requirement, the product selectivities can be tailored by varying the reaction parameters suitably. Several control experiments were also performed the results of which combined with the characterization data allowed to propose a plausible reaction pathway for the formation of 1,2-PeDO.